2020
DOI: 10.1111/ijcp.13610
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of LDL and HDL size and number by nuclear magnetic resonance in a healthy working population: The LipoLab Study

Abstract: Background and aim Atherosclerosis is the underlying process in cardiovascular disease (CVD), the first cause of death in developed countries. We aimed to identify people with no known CVD and normal values of LDL‐C and HDL‐C, but with alterations in the number and size of lipoprotein particles (as measured by nuclear magnetic resonance [NMR]) and to analyse their sociodemographic, clinical and biochemical characteristics. Methods Cross‐sectional study in occupational risks prevention centre in Castellón (Spai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Moreover, intervention studies on cholesterol-lowering therapeutics have shown that reaching optimal cholesterol levels was not enough to eliminate residual risk [4]. These findings have led to further researches on other potential contributors to CHD, such as lipoproteins, and scientists have confirmed that there are atherogenic effects associated with lipoprotein particles [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, intervention studies on cholesterol-lowering therapeutics have shown that reaching optimal cholesterol levels was not enough to eliminate residual risk [4]. These findings have led to further researches on other potential contributors to CHD, such as lipoproteins, and scientists have confirmed that there are atherogenic effects associated with lipoprotein particles [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Among the studied studies, 17 studies had utilized the NMR method to evaluate LDL subfraction. Pallarés et al [ 29 ] in a cross-sectional study conducted on 400 participants, reported that subjects with higher concentrations of small LDL particle size had a higher chance of developing cardiovascular disease. Also, Notarnicola et al [ 30 ] showed that higher concentrations of sdLDL would increase the risk of mortality in patients with CVDs.…”
Section: Resultsmentioning
confidence: 99%
“…Despite previous clinical and cross-sectional studies that have found a positive relationship between higher levels of LDL particles and cardiovascular disease [ 30 , 31 , 32 ], the detailed comparison of compositional proportions and concentrations of different components within LDL particles of varying sizes has not been thoroughly explored. Examining the distribution and compositional characteristics of CH, TG, PL, and other lipid components within LDL particles of various sizes will contribute to a deeper understanding of their potential roles in the development and progression of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%